EVALUATING MONETARY TRANSMISSION MECHANISM IN INDONESIA THROUGH EXCHANGE RATE CHANNEL - Dimas Bagus Wiranata Kusuma (Universitas Muhammadiyah Yogyakarta, 2013)
Abstract:This study aims to evaluate the role of exchange rate channel in transmitting monetary policy effects in Indonesia by addressing the following questions: (i) to what extent is the contribution of the exchange rate in inflation rate fluctuations in Indonesia? (ii) What are the effects of exchange rate channel in explaining the direct pass through effect in Indonesia; and (iii) can the exchange rate channel explain the trade competitiveness in Indonesia? The study utilizes monthly data spanning from January 1990 to April 2009 and is divided into four sub-periods, namely (i) pre-crisis period: January 1990-July 1997; (ii) crisis period: August 1997-December 2000; (iii) post-crisis period: January 2001-June 2005; and (iv) post-ITF period: July 2005-April 2009. By adopting the standard Vector Autoregression model, the study finds changing nature of the exchange rate channel during the various sub-periods of the study.   Abstrak: Studi ini bertujuan mengevaluasi peran saluran nilai tukar dalam mentransmisikan efek kebijakan moneter di Indonesia dengan mengatasi pertanyaan berikut: (i) sampai sejauh mana kontribusi dari nilai tukar fluktuasi tingkat inflasi di Indonesia? (ii) Apa efek dari saluran nilai tukar dalam menjelaskan lulus langsung melalui efek di Indonesia; dan (iii) Dapatkah saluran nilai tukar menjelaskan daya saing perdagangan di Indonesia? Studi ini menggunakan data bulanan mulai dari Januari 1990 sampai April 2009 dan dibagi menjadi empat sub-periode, yaitu (i) periode pra-krisis: Januari 1990-Juli 1997; (Ii) masa krisis: Agustus 1997-Desember 2000; (Iii) periode pasca-krisis: Januari 2001-Juni 2005; dan (iv) pasca-ITF periode: Juli 2005-April 2009. Dengan mengadopsi model Vector Autoregression standar, studi ini menemukan perubahan sifat saluran nilai tukar selama berbagai sub-periode studi.